Intracranial Hypotensive Crisis From an Insidious Spinal Cerebrospinal Fluid-Venous Fistula: A Case Report. Issue 3 (7th June 2021) - Carlstrom, Lucas P; Oushy, Soliman; Graffeo, Christopher S; Perry, Avital; Wijdicks, Eelco F; Bydon, Mohamad; Van Gompel, Jamie; Piepgras, David G
Abstract: BACKGROUND AND IMPORTANCE: Progressive episodic spells of altered levels of consciousness, often advancing to include paroxysmal autonomic instability, may be indicative of a diencephalic dysfunction underlying spontaneous intracranial hypotension (SIH). A rare, and often indolent, etiology may be spinal cerebrospinal fluid (CSF) leak—an elusive diagnosis, especially in cases of CSF-venous fistula (CVF) that are often missed on routine computed tomography (CT) myelography and magnetic resonance imaging (MRI). CLINICAL PRESENTATION: We report an unusual case of a 50-yr-old woman who presented with rapidly progressive cyclical, self-resolving episodes of altered mentation and decreased arousal later in the day. Scrutiny of serial brain MRIs led to a diagnosis of SIH, with severe downward diencephalic and brain stem displacement—resulting in cerebral aqueduct occlusion with obstructive hydrocephalus. Initial clinical improvement occurred with CSF diversion, but the patient quickly deteriorated—developing diencephalic spells, including extensor posturing and severely depressed levels of consciousness. Clinical improvement was seen with stopping CSF diversion and Trendelenburg-positioning. After intensive spinal imaging, dynamic CT myelography identified a left T10 nerve root diverticula and CSF-venous fistula. Surgical obliteration resulted in rapid, profound neurological improvement, and ultimately full neurological recovery by 1 yr. CONCLUSION: In our patient, worsening episodes of confusion, postural headaches, and autonomic instability developed due to SIH, which induced profound downward displacement and compression of the diencephalon and brain stem, and accompanied by subsequent obstructive hydrocephalus. Diagnostic persistence identified the CVF, which had caused the complex multifold pathophysiology and clinical presentation. If suspicion remains high for CVF, persistent spinal imaging, particularly with dynamic myelography, may be crucial.